Validitas Modul Pembelajaran Sistem Peredaran Darah Manusia Berbasis Constructivist Teaching Sequence (CTS) Berbantuan Augmented Reality (AR) - Darti Asriani; Masra Latjompoh; Muh. Nur Akbar; Herinda Mardin; Nurul Fajryani Usman (UNIVERSITAS KHAIRUN, 2025)
The learning module of human circulatory system based on Constructivist Teaching Sequence (CTS) assisted by Augmented Reality (AR) was developed to improve students' understanding of the concept of human circulatory system. This study aims to determine the validity of the developed learning module. This research is a Research and Development (R&D) using the Generic Design Research Model. The instrument used in this research is a module validity sheet assessed by material and media experts. The validation results showed that material validation obtained an average value of 93%, while media validation obtained an average value of 88%, and the module is declared feasible and can be used in learning at school.